Factors associated with type 2 diabetes mellitus in older adults living in Coastal Areas: Implications for community nursing practice - La Indrawan; Sri Susanty; Suhadi Suhadi (Jurnal Keperawatan Padjadjaran, 2025)
Background: Indonesia’s growing older adult population is experiencing a rising burden of type 2 diabetes mellitus (T2DM). Coastal populations face unique risks, including limited health service access, dependence on fisheries-based livelihoods, and dietary patterns high in salt and low in fresh produce. These factors may heighten vulnerability to T2DM, yet remain underexplored. Purpose: This study aimed to examine determinants of T2DM among older adults living in a coastal community. Methods: A cross-sectional study was conducted with 86 older adults selected using purposive sampling between October 30 and December 14, 2024. Data were collected using demographic questionnaires, the Mini Nutritional Assessment (MNA), the Geriatric Depression Scale (GDS), and the Physical Activity Scale for the Elderly (PASE). Chi-square tests assessed associations between independent variables and T2DM, and variables with p < 0.25 were entered into multivariable logistic regression to identify significant predictors. Results: Comorbidity (p < 0.001), nutritional status (p = 0.001), physical activity (p < 0.001), and depression (p < 0.001) were significantly associated with T2DM. In multivariable analysis, lower physical activity emerged as the strongest predictor (OR = 4.13, 95% CI: 1.18–14.48; Wald = 4.92; p = 0.027). Comorbidity (OR = 3.61), depression (OR = 3.64), and nutritional status (OR = 3.28) also remained significant independent factors. Conclusions: T2DM among older adults in coastal areas was more likely in those with comorbidities, depressive symptoms, altered nutritional status, and especially low physical activity. These findings highlight the need for community-based nursing interventions emphasizing physical activity promotion, nutritional counseling, and depression screening to mitigate T2DM risk in vulnerable coastal populations